Weathering of plastics : testing to mirror real life performance - Wypych, George (Society of Plastics Engineers ; Plastics Design Library, 1999)
This book presents findings and opinions of professionals in material degradation testing. The aim is to improve testing methods and procedures. Materials are presented to show that photochemical degradation rate depends on a combination of environmental factors such as UV radiation, temperature, humidity, rain, stress, and concentration of reactive pollutants. The potential effect of each parameter of degradation on data gathered is discussed based on known results from a long experience in testing. This book contains data obtained in laboratories of the largest manufacturers of UV stabilizers and chemical companies which manufacture durable materials. It gives details of testing procedures and choice of parameters of exposure which are crucial for obtaining laboratory results correlating with environmental performance of materials. In addition to exposure conditions, the book contains many suggestions on sample preparation and post-exposure testing. The effective use of these methods shortens testing time of materials and determines acceleration rate of testing.